2020
DOI: 10.1002/cssc.202001600
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of Glycerol to Propanal using Zirconium Phosphate‐Supported Bimetallic Catalysts

Abstract: Selective transformation of glycerol to propanal (PA) provides a feasible route towards the sustainable synthesis of high valueadded chemicals. In this work, zirconium phosphate (ZrP) was studied as support and Ru and Co as metal sites for glycerol hydrogenolysis in a continuous-flow reactor. It was found that ZrP-supported CoÀ O species had a moderate selectivity to PA (49.5 %) in glycerol hydrogenolysis. Notably, once Ru species were doped into CoO/ZrP, the resulting catalyst exhibited not only an outstandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…In contrast to the Ru foil, Ru-phen, Ru-ZrP_0.4, and Ru/α-ZrP displayed higher "white lines", indicating they had higher chemical state than Ru foil (Ru 0 ), agreeing with XPS results (Figure S4 and S6). [73] For Ru-phen, the strong peak at approximately 1.8 Å was attributed to RuÀ Cl coordination shell, while the major peak at 1.5 Å of Ru-ZrP_0.4 catalyst was related to RuÀ O shell (the enlarged region in Figure 8a), [74,75] which revealed that most of chloride ligands in Ru-phen have been substituted by the layer's phosphate groups in the course of intercalation reaction, being consistent with the results of 31 P MAS NMR (Figure 3). In the EXAFS spectra of Ru/α-ZrP, two major peaks centered around 1.5 Å and 1.8 Å respectively related to RuÀ O and RuÀ Cl coordination shells were also observed, indicating that only a small amount of Ruphen complex could also intercalate into ZrP layer even without exfoliation (with RuÀ O and RuÀ Cl shell) (Figure 8a).…”
Section: Identification Of Active Sites In Ru-phen Complex Intercalated Zrp Catalystsmentioning
confidence: 99%
“…In contrast to the Ru foil, Ru-phen, Ru-ZrP_0.4, and Ru/α-ZrP displayed higher "white lines", indicating they had higher chemical state than Ru foil (Ru 0 ), agreeing with XPS results (Figure S4 and S6). [73] For Ru-phen, the strong peak at approximately 1.8 Å was attributed to RuÀ Cl coordination shell, while the major peak at 1.5 Å of Ru-ZrP_0.4 catalyst was related to RuÀ O shell (the enlarged region in Figure 8a), [74,75] which revealed that most of chloride ligands in Ru-phen have been substituted by the layer's phosphate groups in the course of intercalation reaction, being consistent with the results of 31 P MAS NMR (Figure 3). In the EXAFS spectra of Ru/α-ZrP, two major peaks centered around 1.5 Å and 1.8 Å respectively related to RuÀ O and RuÀ Cl coordination shells were also observed, indicating that only a small amount of Ruphen complex could also intercalate into ZrP layer even without exfoliation (with RuÀ O and RuÀ Cl shell) (Figure 8a).…”
Section: Identification Of Active Sites In Ru-phen Complex Intercalated Zrp Catalystsmentioning
confidence: 99%
“…[1][2][3] The renewability and unique structure of glycerol make it a versatile platform molecule for producing a variety of fine chemicals via catalytic reactions, such as hydrogenolysis, oxidation, dehydration, esterification and others. [4][5][6][7][8] 1,3-propanediol (1,3-PDO) is an important chemical from glycerol hydrogenolysis with wide applications in the manufacture of polytrimethylene terephthalate, polyurethanes, and cyclic compounds. [9,10] n-Propanol (n-PO) is another valuable derivative from glycerol and is widely used as a solvent, pharmaceutical or pesticide intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] n-Propanol (n-PO) is another valuable derivative from glycerol and is widely used as a solvent, pharmaceutical or pesticide intermediate. [8] The current market price of glycerol hydrogenolysis products ranks from high to low as 1,3-PDO > n-PO > 1,2-PDO. [11] Thus, the direct hydrogenolysis of glycerol into n-PO has also attracted much attention recently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations